Characterization of α-isopropylmalate synthases containing different copy numbers of tandem repeats in Mycobacterium tuberculosis - Palittapongarnpim Prasit (BMC Microbiology, 2009)
Abstract Background Alpha-isopropylmalate synthase (α-IPMS) is the key enzyme that catalyzes the first committed step in the leucine biosynthetic pathway. The gene encoding α-IPMS in Mycobacterium tuberculosis, leuA, is polymorphic due to the insertion of 57-bp repeat units referred to as Variable Number of Tandem Repeats (VNTR). The role of the VNTR found within the M. tuberculosis genome is unclear. To investigate the role of the VNTR in leuA, we compared two α-IPMS proteins with different numbers of amino acid repeats, one with two copies and the other with 14 copies. We have cloned leuA with 14 copies of the repeat units into the pET15b expression vector with a His6-tag at the N-terminus, as was previously done for the leuA gene with two copies of the repeat units. Results The recombinant His6-α-IPMS proteins with two and 14 copies (α-IPMS-2CR and α-IPMS-14CR, respectively) of the repeat units were purified by immobilized metal ion affinity chromatography and gel filtration. Both enzymes were found to be dimers by gel filtration. Both enzymes work well at pH values of 7–8.5 and temperatures of 37–42°C. However, α-IPMS-14CR tolerates pH values and temperatures outside of this range better than α-IPMS-2CR does. α-IPMS-14CR has higher affinity than α-IPMS-2CR for the two substrates, α-ketoisovalerate and acetyl CoA. Furthermore, α-IPMS-2CR was feedback inhibited by the end product l-leucine, whereas α-IPMS-14CR was not. Conclusion The differences in the kinetic properties and the l-leucine feedback inhibition between the two M. tuberculosis α-IPMS proteins containing low and high numbers of VNTR indicate that a large VNTR insertion affects protein structure and function. Demonstration of l-leucine binding to α-IPMS-14CR would confirm whether or not α-IPMS-14CR responds to end-product feedback inhibition.